1999
DOI: 10.1029/99eo00153
|View full text |Cite
|
Sign up to set email alerts
|

Even more interdisciplinary future lies ahead for ocean chemistry

Abstract: covering approximately 30 km X 30 km. December 18-28,1998, subglacial eruption. These images were acquired at a radar incidence angle of approximately 50° in an ascending (right-looking) geometry. Fig. 1. RADARSAT synthetic aperture radar images of the Grimsvotn region of the Vatnajokull ice cap, southern Iceland, acquired before (left), during (middle), and after (right) the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although there are a limited number of studies that quantify these fluxes, the results suggest that the fluxes may be important globally. The Future of Ocean Chemistry (FOCUS) workshop sponsored by NSF concluded that land‐sea exchange at ocean margins and advective chemical transport through sediments and coastal aquifers would be among the major themes to be addressed during the next few decades [ Mayer et al , 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a limited number of studies that quantify these fluxes, the results suggest that the fluxes may be important globally. The Future of Ocean Chemistry (FOCUS) workshop sponsored by NSF concluded that land‐sea exchange at ocean margins and advective chemical transport through sediments and coastal aquifers would be among the major themes to be addressed during the next few decades [ Mayer et al , 1999].…”
Section: Introductionmentioning
confidence: 99%